Complementary ab initio and X-ray nanodiffraction studies of Ta2O5. (15th January 2015) - Hollerweger, R.; Holec, D.; Paulitsch, J.; Bartosik, M.; Daniel, R.; Rachbauer, R.; Polcik, P.; Keckes, J.; Krywka, C.; Euchner, H.; Mayrhofer, P.H.
Abstract: The complex structure of Ta2 O5 led to the development of various structural models. Among them, superstructures represent the most stable configurations. However, their formation requires kinetic activity and long-range ordering processes, which are hardly present during physical vapor deposition. Based on nano-beam X-ray diffraction and concomitant ab initio studies, a new metastable orthorhombic basic structure is introduced for Ta2 O5 with lattice parameters a = 6.425 Å, b = 3.769 Å and c = 7.706 Å. The unit cell containing only 14 atoms, i.e. two formula unit blocks in the c direction, is characterized by periodically alternating the occupied oxygen site between two possible positions in succeeding 002-planes. This structure can be described by the space group 53 ( Pncm ) with four Wyckoff positions, and exhibits an energy of formation of −3.209 eV atom −1 . Among all the reported basic structures, its energy of formation is closest to those of superstructures. Furthermore, this model exhibits a 2.5 eV band gap, which is closer to experimental data than the band gap of any other basic-structure model. The sputtered Ta2 O5 films develop only a superstructure if annealed at temperatures >800 °C in air or vacuum. Based on these results and the conveniently small unit cell size, it is proposed that the basic-structure model described here is an ideal candidate for both structure and electronic state descriptions of orthorhombic Ta2 O5 materials.